Pengembangan Skala Adversity Quotient pada Siswa Sekolah Menengah Pertama - I Putu Agus Wira Pratama; I Ketut Gading; Kadek Ari Dwiarwati (Universitas Pendidikan Ganesha, 2021)
Penelitian ini bertujuan untuk mengetahui, prototype, validitas dan reliabilitas skala adversity quotient siswa sekolah menengah pertama. Metode dalam penelitian ini menggunakan metode Research and Development dan menggunakan desain penelitian Borg & Gall yang terdiri dari 10 tahap yaitu: Research and information colleting, Planing, Develop preliminary from of product, Preliminary filed, Main product revision, Main filed testing, Operational product revision, Operational filed testing, Final product revision, Dissemination and implementation. Uji validitas isi, dalam penelitian ini menggunakan formula Lawshe dengan hasil CVR=1 dan CVI=1. Pada uji validitas internal konsistensi butir dalam penelitian ini diperoleh nilai rxy =0,34 dengan 40 item yang dinyatakan valid, dan ditemukan hasil uji reliabilitas dengan formula Crombach’s Alpha diperoleh hasil reliabilitas=0,86 dengan kategori reliabilitas sangat tinggi. Hasil 200 respon siswa yang telah menjawab kuesioner skala adversity quotient yaitu sebanyak 37 siswa dengan kategori adversity quotient rendah, 173 dengan kategori sedang dan 31 siswa dengan kategori tinggi. Abstract: This study aims to determine the prototype, validity and reliability of the adversity quotient scale of junior high school students. The method in this study uses the Research and Development method and uses the Borg & Gall research design which consists of 10 stages, namely: Research and information colleting, Planing, Develop preliminary from product, Preliminary filed, Main product revision, Main filed testing, Operational product revision , Operational filed testing, Final product revision, Dissemination and implementation. Content validity test, in this study using the Lawshe formula with the results CVR=1 and CVI=1. In the internal validity test of the consistency of the items in this study, the value of rxy = 0.34 with 40 items declared valid, and the results of the reliability test with the Crombach's Alpha formula obtained reliability results = 0.86 with a very high reliability category. The results of 200 student responses who have answered the adversity quotient scale questionnaire are 37 students in the low adversity quotient category, 173 in the medium category and 31 students in the high category.